Evaluation of Sexual Dysfunction in Patients Undergoing Hemodialysis Treatment. - Bayram, Rıdvan; Yıldız, Hicran; Karaca Sivrikaya, Sibel (Sexuality & Disability, 2021)
Aim: In this study. it was aimed to determine the prevalence of sexual dysfunction (SD) and the factors that may affect the occurrence of SD in patients receiving hemodialysis treatment. Methods: The sample of the study consists of 49 patients (20 females. 29 males) receiving treatment in the hemodialysis unit of a university hospital. The data of the study were collected through a general information form including socio-demographic characteristics and risk factors. Female Sexual Function Index (FSFI). International Assessment Form for Erectile Function (IIEF) and Quality of Life Scale (SF-36). Results: In our study. SD was detected in all patient groups. While the most affected area was seen to be orgasmic function and the least affected area was sexual desire in famales. the most affected area was found to be orgasmic function and the least affected area was erectile dysfunction in males. Such factors as age. profession. having a child. working status and duration of hemodialysis were found to affect occurrence of SD. There was a relationship between all sub-dimensions of sexual function and quality of life in male and female subjects. Conclusion: In conclusion. sexual dysfunction is commonly encountered in patients undergoing hemodialysis treatment. In these patients. psychosocial factors as well as disease-related factors have an effect on SD. Therefore. SD should be evaluated together with disease-related factors as well as psychosocial factors in patients undergoing hemodialysis treatment.